Sociodemographic Determinants and Common Reasons for Visiting the Emergency Dental Service in the City of Zagreb - Antonija Balenović; Alem Fazlić; Marko Mihelčić; Andrea Hoch; Vedran Radujković (Acta Stomatologica Croatica, 2019)
Objective: The objective of the study was to determine the sociodemographic and clinical parameters of patients who visit the emergency dental service and their most common diagnoses. Materials and Methods: The data were collected on the basis of a survey filled out by patients. A total of 1730 out of 6732 patients (26%) were surveyed using a questionnaire to analyze sociodemographic status, dental visits, the description and dynamics of the symptoms. After the data collection, methods of descriptive data presentation and of inferential statistics were made in SPSS. Results: Survey results show that most subjects (60.4%) came during the weekends and holidays. The subjects, 73.1 % of them, stated that they had already used this type of service, and 65.8% did not visit their dentist beforehand. The largest number of subjects (62.2%) reported that they needed emergency service within a week after their problems had begun. The most common diagnoses included face and jaw abscesses (27.3%). There is a statistically significant difference between the number of patients who went to the emergency dental service and completed the questionnaire over the course of several months contrary to patients who were there in May and June (59.7%) compared to July and August (40.3 %). Conclusions: Most subjects had clear indications for being referred to an emergency dental service. Most of the emergency conditions were mainly due to irregular visits to the dentist. Patient education and preventive programs would probably have reduced the number of visits.